5. Uluslararasi Istanbul Bienali. - 5th International Istanbul Biennial (Istanbul : Istanbul Foundation for Culture and Arts, 1998)
Ahtila, Eija-Liisa ; Alaez, Ana Laura ; Almeida, Helena ; Altindere, Halil ; Antoni, Janine ; Ataman, Kutlug ; Avgar, Vahap ; Funk, Lexy ; Sükran, Aziz ; Berksoy, Semiha ; Isaeus-Berlin, Meta ; Eszter Bodnar, Eva ; Bony, Oscar ; Bourgeois, Louise ; Bournigault, Rebecca ; Buetti, Daniele ; van Caeckenbergh, Patrick ; Cattelan, Maurizio ; Creten, Johan ; Cross, Dorothy ; Davids, Yael ; Diller + Scofidio ; Durham, Jimmie ; Eliasson, Olafur ; Emin, Tracey ; Erdem, Türkan ; Feyzdjou, Chohreh ; François, Michel ; etc.
5th International Istanbul Biennial, October 5 - November 9, 1997
boek